Role of Insects in the Environment and their Adaptations in Special Reference to Terrestrial Environment - Samreen; Mandla, Rajashekhar (Chronicle of Bioresource Management, 2024)
Insects are the most abundant creatures on the earth and found to reside in all kinds of environment from extreme hot springs to freezing snow caps which makes them the most wondrous organisms due to their impeccable body size, ability to fly, hexapod locomotion, decentralized nervous system, malphigian tubules as excretory organs and etc. Insects are known to play a very important role in various ecological processes such as pollination, predation/parasitism, ecosystem cycling, insects as food and decomposition. Insects have the capability to adapt to different environmental stresses like low temperatures, high temperatures and adopt morphological, behavioural and physiological adaptation strategies for their survival. This article gives insights regarding the important role of insects in ecological processes and their adaptations in terrestrial environment.